Investigating the Factors Affecting Violence against Emergency Nurses in Sabzevar Medical Sciences Hospitals - Alemeh DEHNABI; Hamid RADSEPEHR; Atefeh DEHNABI (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Workplace violence in the health system has become an important issue in policy making in recent years. It is one of the most important and complex issues in the health system. The purpose of this study was to investigate the factors affecting workplace violence in emergency nurses. Methods: The present study was descriptive-analytic which was done on 100 emergency nurses of Sabzevar educational Medical Sciences hospitals who were selected using the available sampling method. Data were collected using a WHO-adjusted questionnaire which consisted of 4 sections (demographic information (11 questions), threats (10 questions), verbal violence (10 questions) and physical (12 questions). The data were analyzed using descriptive and inferential statistics (chi-squared test and Fisher exact). Data were entered into the statistical software of SPSS17. Results: The findings revealed that during the six-month period, nurses reported 92 cases of verbal abuse (59.78%), physical (19.56%), racial (15.21%) and sex (5.43%). The most important factors in the incidence of violence against nurses were the availability of nurses (55.43%), lack of motivation and job satisfaction in nurses (50%) and health concerns about the patient or companions (42.39%). Violence against male nurses was higher than that of women. Furthermore, the most common cause of violence against nurses was the companions of the patient. Conclusion: The results of this study confirmed the high prevalence of workplace violence among hospital nurses. Therefore, it can be suggested by improving nurses' communication skills, teaching their patients and their companions and serious follow-up of cases of violence against nurse, can reduce violence and improve health care services.